Knowledge-related Human Papillomavirus Vaccination: A Study of Indonesian Women - Astri Mutiar; Tiara Wulandari; Nunung Nurhayati; Dewi Marfuah; Suci Noor Hayati (STIKep PPNI Jawa Barat, 2023)
Aims: Human papillomavirus (HPV) is a sexually transmitted virus that can lead to various diseases, most known as cervical cancer’s etiology. HPV vaccination is one of the primary prevention strategies to reduce HPV transmission. To increase vaccination rates, it is essential that women have a good knowledge of receiving the HPV vaccine. The purpose of the study was to explore the knowledge of HPV vaccination among Indonesian women. Methods: A cross-sectional study was conducted among 462 Indonesian women recruited by convenience sampling on March to May 2022. The adapted questionnaire of knowledge with 28 items was used with Cronbach's Alpha score estimated at 0.838. Women who are 15 to 49 years old, able to understand and speak the Indonesian language, and have a gadget were included in this study. Women who already get HPV vaccination are excluded. Univariate statistics were used to describe Indonesian women’s knowledge of HPV Vaccination. Results: The research shown that the mean age of the respondents is 23.17± 5.065. Half of the respondent level of education is college as many as 245 people (53%). Half of the respondents are employed as many as 239 people (51.7%). The average knowledge is 16.02 with a standard deviation (SD) of 6.43, the knowledge value indicates less knowledge of HPV vaccination among women. In the item analysis, found that most respondents answer incorrectly to the question “HPV testing is done to show whether the HPV vaccine is needed?